(3GdGYJHGQ HHbGA GdLfI hGdfGQs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s ((3GdeOQSI GdYGOdjI (B_ (3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf GYJbGO GdeSdejf Gf GdLfI hGdfGQ s
(3BNQgG (B:s
(3hgh YeOg Ggd GdcdGe fSCd Gddg GdYGajI hGdSdGeI Edi gfG JeGe GdQSGdI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B118s
Keywords: (3GdJhMjO hGdedd hGdfMds